Degradation and conversion of endosulfan by newly isolated Pseudomonas mendocina ZAM1 strain - Mir, Zahoor A. (3 Biotech, 2017)
Endosulfan contamination is one of the major concerns of soil ecosystem, which causes detrimental effects not only to humans but also to animals and plants. Therefore, the aim of this study was to isolate and identify a novel bacterial strain capable of degrading endosulfan in agriculture contaminated soils. A novel bacterial strain was isolated from the sugarcane field contaminated with endosulfan, and was named as ZAM1 strain. The ZAM1 bacterial strain was further identified as Pseudomonas mendocina based on the biochemical and molecular analysis. 16sRNA sequence analysis of ZAM1 strain shows maximum similarity with known endosulfan-degrading bacteria (Pseudomonas putida), respectively. Enrichment was carried out using the endosulfan as sole sulfur source. The ZAM1 strain was able to use α and β endosulfan as a sole sulfur source. Our results showed that ZAM1 strain degrades endosulfan >64.5% (50 mg/l) after 12 days of incubation. The residues were analyzed by GC–MS analysis and confirmed the formation of metabolites of dieldrin, 2 heptanone, methyl propionate, and endosulfan lactone compounds. Hence, these results indicate that the ZAM1 strain is a promising bacterial source for detoxification of endosulfan residues in the environment.